Physico-Mechanical Analysis of Free Ethylcellulose FilmsPlasticized with Incremental Weight Percents of Dibutyl Sebacate: Ethylcellulose membranes plasticized with dibutyl sebacate - Sogol Kangarlou; Ismaeil Haririan (Iranian Journal of Pharmaceutical Sciences, 2007)
This research was conducted to investigate the physico-mechanical characteris-tics of the ethylcellulose-based coating membranes plasticized with different weightpercents of dibutyl sebacate. In this experiment, free thin polymer sheetings of thesample formulations, by incorporating incremental weight percents of the plasticizer,were prepared employing a revised casting method of delayed solvent evaporation,whereby similar flat specimens of standard dimensions were subjected to tensileloadings and extensions. The data were analyzed to fairly decide on a moderateconcentration of the plasticizer to provide a rationale explanation of a strong, hard,and tough structure among the specimens. The data revealed that 40% (w/w) of theester results in the toughest structure amongst the similar specimens of the seriesleading to an ultimate toughness of 3.31 mj/m3.